2014
DOI: 10.1080/09669760.2014.988208
|View full text |Cite
|
Sign up to set email alerts
|

Children's early numeracy in Finland and Iran

Abstract: This research investigates similarities and differences in young children's early numeracy skills related to age, nationality and gender. The participants were five-to seven-year-old children from Finland and Iran. Early numeracy was investigated by using tasks measuring number-related relational skills (e.g. comparison, one-to-one correspondence) and counting skills (e.g. enumeration, number-word sequence skills). A hybrid multigroup, multiple-indicator-multiple-cause (MIMIC) approach to factorial invariance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
2
10
1
Order By: Relevance
“…They stated that the mistakes of young children when they are counting are caused by the method these authors used and by cardinal numbers. In addition to these results, subsequent researchers have revealed the influence of culture in cardinal number acquisition (Campbell and Xue, 2001;Sarnecka et al, 2007;Aunio et al, 2014;Cankaya et al, 2014). In this study, we aimed to contribute to the discussion in the literature by examining the acquisition of cardinal numbers by Turkish children.…”
Section: Introductionmentioning
confidence: 92%
“…They stated that the mistakes of young children when they are counting are caused by the method these authors used and by cardinal numbers. In addition to these results, subsequent researchers have revealed the influence of culture in cardinal number acquisition (Campbell and Xue, 2001;Sarnecka et al, 2007;Aunio et al, 2014;Cankaya et al, 2014). In this study, we aimed to contribute to the discussion in the literature by examining the acquisition of cardinal numbers by Turkish children.…”
Section: Introductionmentioning
confidence: 92%
“…The countries were purposely selected so that participants would differ in school entrance age but would have relatively similar, middle-SES western European backgrounds. Previous cross-cultural comparisons of early mathematical skills typically showed similar early mathematical skills when comparing children from countries with similar cultural backgrounds (Aunio, Korhonen, Bashash, & Khoshbakht, 2014;Van de Rijt et al, 2003). Our selection of the sample allowed us to identify the effect of formal schooling on mathematical skill profiles.…”
Section: Limitationsmentioning
confidence: 98%
“…Already prior to formal education, most children can perform basic verbal addition and subtraction tasks of small numbers (Aunio et al, 2014). In order to perform these rudimentary calculations, children develop various strategies known as counting strategies; sum, min, decomposition and fact retrieval (Geary & Hoard, 2005;Siegler & Shrager, 1984).…”
Section: Arithmeticmentioning
confidence: 99%
“…Cross-cultural research has shown that most children from numerate societies are capable of performing basic addition and subtraction, even prior to formal education (Aunio, Korhonen, Bashash, & Khoshbakht, 2014). However, there is also large individual variation in mathematical comprehension and performance.…”
Section: Introductionmentioning
confidence: 99%